The Effect of the H1N1 Pandemic on Learning : What to Expect with COVID-19 - Amorim, Vivian; Piza, Caio; Lautharte Junior, Ildo Jose (World Bank, Washington, DC, 2020)
The analysis indicates that the extension of the winter break, adopted in 13 municipalities of the state of Sao Paulo during the H1N1 pandemic, significantly decreased learning outcome among students in the 5th grade of elementary school (ES). The decrease in math performance resulting from the two to three weeks winter break extension is equivalent to two months of learning. The impacts were more pronounced among schools in the bottom quintile of test score distribution, which suggests that the consequences were more severe among the most vulnerable groups. These results suggest that the effect of COVID-19 (coronavirus) will be relevant, and remedial policies will be required to mitigate learning losses.